2010
DOI: 10.1007/s11104-010-0506-z
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition rates of bryophytes in managed boreal forests: influence of bryophyte species and forest harvesting

Abstract: The slow decomposition rate of boreal forest floor bryophytes contributes both to maintaining high soil C reserves as well as affecting conditions for tree growth by maintaining excessively high soil water content, cooling the soil and slowing nutrient cycles. In this study, mass loss of three bryophyte species (Pleurozium schreberi, Sphagnum capillifolium, S. fuscum) was measured in unharvested, partial cut and low-retention cut forest blocks. Mesh decomposition bags containing the three species and wood stic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 58 publications
1
24
1
Order By: Relevance
“…These reference samples were also used to establish the relationship between the fresh weight (saturated conditions) and dry weight of individual moss cushions (Table S1). The mosses were therefore cleaned from litter and any other moss species present, saturated by submerging in water for at least 30 minutes, spun with 20 pulses for approximately one minute to release external water according to Fenton et al [59], weighed (to obtain the fresh weight) and then oven dried (70 °C, 48 hours) and weighed again to get the oven-dry weight. Table S1.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…These reference samples were also used to establish the relationship between the fresh weight (saturated conditions) and dry weight of individual moss cushions (Table S1). The mosses were therefore cleaned from litter and any other moss species present, saturated by submerging in water for at least 30 minutes, spun with 20 pulses for approximately one minute to release external water according to Fenton et al [59], weighed (to obtain the fresh weight) and then oven dried (70 °C, 48 hours) and weighed again to get the oven-dry weight. Table S1.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Similarly, stands with a closed canopy tend to be dominated by feather mosses [66], which have a lower photosynthetic compensation point than Sphagnum species [67]. Our studies showed a positive feedback loop in the paludification process: as stands open up through natural self-thinning, Sphagnum species dominate and replace feather mosses [66], stimulating the accumulation of the organic layer via their slow decomposition rate [59,60] and their faster growth rate [68]. This thick organic layer results in an elevated water table [66], which creates a wet, cold, nutrient poor rooting environment for trees.…”
Section: The Stand/plot Levelmentioning
confidence: 62%
“…Studies have shown that not only do feather mosses (such as P. schreberi) harbour N fixing cyanobacteria [57], but also that black spruce is able to absorb this organic N [58]. Furthermore, Sphagnum species have particularly slow decomposition rates [59,60], which are not fully explained by their high C:N, but are probably a function of various secondary metabolites that limit microbial breakdown of their cell walls [61]. This fundamental knowledge raised questions that needed to be addressed at a coarser scale of analysis: what are the drivers of paludification at the site level, and what are the best techniques to manage paludified stands?…”
Section: The Tree and Plant Levelmentioning
confidence: 99%
“…Nordic coniferous forests often have a several cm thick moss cover on the ground. Moss plants produce considerable amounts of litter and the moss litter of boreal forest floors decomposes slowly [37,38]. At the present study site, moss litter was easily defined in layers which were at least six years old [17].…”
Section: Suggestions For Future Researchmentioning
confidence: 68%